2008
DOI: 10.1179/174328407x179773
|View full text |Cite
|
Sign up to set email alerts
|

Influence of post-weld heat treatments on microstructure and mechanical properties of AISI 431 martensitic stainless steel friction welds

Abstract: The relative effects of different post-weld heat treatments (PWHTs) on microstructure and mechanical properties of friction welded martensitic stainless steel type AISI 431 were studied. The weld microstructure consists of acicular martensite in equiaxed prior austenite grains and with heat treatment, the martensitic microstructure experiences coarsening. It was observed that retained austenite content decreases with an increase in the PWHT tempering temperature. The tensile properties of welds under different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…15). These observations are in conformity with similar trends reported in steels and titanium alloys [22][23][24]. Lower toughness of welds as compared to the parent metal could be due to presence of less number of martensite colonies that contribute to crack path deviation.…”
Section: Impact Toughnesssupporting
confidence: 89%
“…15). These observations are in conformity with similar trends reported in steels and titanium alloys [22][23][24]. Lower toughness of welds as compared to the parent metal could be due to presence of less number of martensite colonies that contribute to crack path deviation.…”
Section: Impact Toughnesssupporting
confidence: 89%
“…18). These observations are in conformity with similar trends reported in steels and titanium alloys [19,20]. The present observations suggest that post-weld homogenization treatment that results in elimination of micro-segregation leading to elimination of reverted austenite is required to improve the impact toughness of welds.…”
Section: Impact Toughnesssupporting
confidence: 93%
“…and increase toughness. Either annealing and normalizing or tempering has been tried by many researchers [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In the studies by Raja Sekhar [4], friction-welded component of AISI 431 martensitic stainless was post-tempered at 400 °C and it is reported that martensitic microstructure got coarsened which resulted in high strength and hardness but the poor impact toughness. Emre and Kacar [5] conducted friction welding studies with pipes made of N80 and 42CrMo4 steels and recommended annealing at 600 °C for 20 min.…”
Section: Introductionmentioning
confidence: 99%